Tourism in the Slovak Republic - Ščepánová, Petra (Hotel and Tourism Management, 2014)
The presented article offers an overview of Slovak tourism and its recent development in terms of visitors, expenditures and value added to the national economy of the Slovak Republic. The goal of the article is to provide a snapshot of the tourism industry based on main indicators of the tourism sector with a short introduction into the touristic potential of Slovakia for its visitors. For this purpose, statistical data mainly of the Slovak Statistics Office is used descriptively. Despite its smaller size, Slovakia is rich with cultural, historical and natural assets, but also with potential for future improvement and development of the tourism services sector, with only a 3% contribution to the value added. Untapped resources in the area of tourism have unused potential for important contributions to the national economy, but especially to the regional and local economy of rural areas in terms of providing employment, securing development and raising living standards.